Integrating Digital Tools for Enhanced Teaching and Learning Effectiveness in Business Education: Strategies and Implications for 21st-Century Skill Development - Abubakar, Ibrahim Mohammed; Paris, Adama Suleiman; Sambo, Farida Gidado (Lembaga Yasin AlSys, 2025)
This study examines the integration of digital tools in business education and their impact on teaching and learning effectiveness, with a particular focus on strategies employed and implications for 21st-century skill development. Utilizing a survey research design, data were collected from 300 business education lecturers across colleges in North Central Nigeria. The findings reveal that educators regularly incorporate digital tools such as PowerPoint presentations, educational videos, online learning management systems, and digital quizzes to enhance instructional delivery. Pedagogical strategies including collaborative assignments, flipped classrooms, blended learning, and gamification were identified as effective methods for embedding digital technologies into teaching practices. The integration of these tools was found to significantly support students’ development of critical 21st-century competencies, notably communication, critical thinking, creativity, and problem-solving. The study underscores the importance of sustained professional development, robust digital infrastructure, and supportive institutional policies to optimize the benefits of technology-enhanced instruction in business education. The findings contribute to the growing body of literature on digital pedagogy and offer practical recommendations for educators, administrators, and policymakers to advance effective digital integration in higher education.